Postpartum Spontaneous Subcapsular Hepatic Hematoma Related to Preeclampsia. (16th August 2014) - Anyfantakis, Dimitrios; Kastanakis, Miltiades; Fragiadakis, Georgios; Karona, Paraskevi; Katsougris, Nikolaos; Bobolakis, Emmanouil
Abstract : Subcapsular hematoma of the liver represents an unusual clinical phenomenon in the pregnancy and postpartum period with serious complications in terms of fetal and maternal mortality. Here we report a case of a 32-year-old primiparous female at 36 weeks of gestation, admitted to a maternity ward of a private clinic for preeclampsia. The woman underwent an emergency caesarean section with the extraction of an alive foetus. A few hours after delivery, she was transferred to the emergency department of our institution complaining of severe epigastric pain. Diagnostic work-up was suggestive of a subcapsular right lob hepatic hematoma which was successfully managed conservatively. Timely diagnosis is necessary for the prevention of life-threatening events in mother and fetus. For this reason acute care physicians have to be vigilant of the condition and consider this in the differential diagnosis of epigastric pain during pregnancy and postpartum.